Kin support and the English poor: evidence from Lancashire, c.1620–17101. Issue 256 (1st March 2019) - Healey, Jonathan
Abstract: The 'nuclear hardship hypothesis', argued by Peter Laslett in 1988, holds that that the prevalence of the nuclear household in early modern England, and the apparent weakness of kinship interactions outside it, left the burden of caring for the vulnerable squarely on the 'collectivity', most obviously in the form of the Elizabethan poor law. But recent studies of family and kinship in English society have questioned the idea of the autonomous nuclear household, challenging us to reconsider this notion from the perspective of the early modern poor. This article uses a largely untapped set of sources, pauper petitions, to look for qualitative evidence of kinship support among the seventeenth‐century English poor. Focusing on the county of Lancashire, this article mines petitions for references to kinship support, to the forms it took, and to what it 'meant' to recipients. It argues that kinship support was not uncommon, and indeed was the expected social norm where it was physically available. But it had clear limits, and might only be a temporary expedient; moreover, most recorded examples saw support flowing between former members of the same nuclear household.